Prevention of erosive and ulcerative gastroduodenal bleeding in patients after endovascular surgery on the arteries of the lower extremities for critical ischemia - A. A. Poliantsev; D. V. Frolov; A. M. Linchenko; S. N. Karpenko; O. A. Kosivtsov; A. A. Chernovolenko; E. V. Kaplunova (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to evaluate methods for the prevention of gastrointestinal bleeding in patients after endovascular surgery on the arteries of the lower extremities for critical ischemia.METHODS AND MATERIALS. The study included 188 patients treated in the vascular surgery department of A. A. Polyantsev General Surgery Clinic of Volgograd State Medical University for obliterating atherosclerosis of the arteries of the lower extremities in the period from 2017 through 2021.RESULTS. There was a relationship between the indicator that the patient indicated independently – the number of painkillers taken per day to reduce pain, and erosive and ulcerative lesions of the stomach and duodenum in both groups. The increasing number of operations with critical lower extremity ischemia (СLEI) and the expected decrease in the number of amputations indicates the increased capabilities of vascular and X-ray endovascular surgeons in preserving the extremity and ultimately the life of patients with decompensated forms of obliterating lesions of the extremities. This group of patients had a large number of perioperative complications from various organs and systems, including a high probability of gastrointestinal bleeding.CONCLUSION. An increased risk group for the occurrence of gastrointestinal bleeding (GIB): patients with repeated reconstructions, surgical corrections of complications or amputations at various levels, as well as taking anticoagulants in therapeutic dosage. Long-term routine prevention of acute erosive and ulcerative lesions of the stomach and duodenum, gastrointestinal bleeding with proton pump inhibitors is not acceptable for this group of patients. It is necessary to have a complex effect on the factors of aggression – the exclusion of the use of NSAIDs, total eradication.